2019
DOI: 10.1063/1.5086925
|View full text |Cite
|
Sign up to set email alerts
|

Combining high-energy X-ray diffraction with Surface Optical Reflectance and Planar Laser Induced Fluorescence for operando catalyst surface characterization

Abstract: We have combined three techniques, High Energy Surface X-Ray Diffraction (HESXRD), Surface Optical Reflectance, and Planar Laser Induced Fluorescence in an operando study of CO oxidation over a Pd(100) catalyst. We show that these techniques provide useful new insights such as the ability to verify that the finite region being probed by techniques such as HESXRD is representative of the sample surface as a whole. The combination is also suitable to determine when changes in gas composition or surface structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…It should also be noted that there is an initial “jump” in reflectivity loss as the grains transition into the active regime, as shown in the magnified region of panel (b). This is consistent with previous studies 17 , 18 and may be due to a thinner layer of oxide forming as the gas composition changes when the reactant gases are depleted by the chemical reaction. Other details of note are the spatial gradients visible on the edges of some of the grains in panel (e), for example, the one at the tip of the red arrow.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It should also be noted that there is an initial “jump” in reflectivity loss as the grains transition into the active regime, as shown in the magnified region of panel (b). This is consistent with previous studies 17 , 18 and may be due to a thinner layer of oxide forming as the gas composition changes when the reactant gases are depleted by the chemical reaction. Other details of note are the spatial gradients visible on the edges of some of the grains in panel (e), for example, the one at the tip of the red arrow.…”
Section: Resultssupporting
confidence: 93%
“…This would build on previous studies where PLIF has been combined with 2D-SOR on single crystals. 16 , 17 It would then be possible to directly correlate a local change in the reflectivity with a local change in catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has moreover been found that even the catalyst surface of a single crystal model catalyst may not always behave homogeneously, e.g. due to inhomogeneous gas distributions around the sample [144], a technique that visualizes the surface morphology/optical properties of the whole sample surface at the same time is essential.…”
Section: Surface Optical Reflectance (Sor)mentioning
confidence: 99%
“…Instrum. 90 033703 (2019) [133], with the permission of AIP Publishing. sapphire reactor dome [133].…”
Section: Surface Optical Reflectance (Sor)mentioning
confidence: 99%
“…Consequently, this combination of integral activity measurements with single point probing of catalyst material state is prone to produce erroneous structure-function relationships 9,10 . In attempts to alleviate this problem, recent studies have used a combination of techniques to both spatially and temporally investigate model 3,[11][12][13][14][15][16][17] and more complex catalysts 9,11,12,[18][19][20][21][22] , with several comprehensive reviews on the topic published recently 2,9,10,23 . For example, the thin 150 μm capillary used in Spaci-MS 2 enables spatiotemporal characterization of reactant gradients with a spatial resolution of ca.…”
mentioning
confidence: 99%